Re-inventarisation of fish in the Sail River, Pekanbaru Regency, Riau province - Adilla Yusra Lubis; Efawani '; Windarti ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Sail River is one of the polluted rivers in Riau. A study on fish identification in that river has been conducted in 1981 (Hamidy and Alawi, 1991) and there were 54 species present. The environmental changing during these recent years, however, may affects the fish population in that river in general. To understand the fish type present in the Sail River nowadays, a study has been conducted in December 2014 - February 2015. The fish was sampled from 5 study sites, there were in the upstream of river, under the Imam Munandar bridge, under the Sail bridge, in the Lima Puluh District and in the river mouth of the river. The fish were caught using gill net, lure, and cash net. Fish species are identified based on Saanin (1986) and Kottelat et al. (1993). Results shown that the fish caught during the study were consisted of Cypriniformes (8 species), Osteoglosiformes (1 species), Siluiformes (2 species), Beloniformes (1 species), Cyprinodontiformes (1 species), and Perciformes (10 species). The most common genus was Cypriniformes and Perciformes, and they were captured mostly under the Imam Munandar bridge. Based on data obtained, it can be concluded that the fish species living in the Sail River has been significantly decreased during the last 25 years.Key word : Sail river, Pekanbaru, cypriniformes, perciformes, fish population decrement